Rikkunshito, a ghrelin potentiator, ameliorates anorexia–cachexia syndrome - Fujitsuka, Naoki; Uezono, Yasuhito (Frontiers in Pharmacology, 2014)
Anorexia-cachexia syndrome develops during the advanced stages of various chronic diseases in which patients exhibit a decreased food intake, weight loss, and muscle tissue wasting. For these patients, this syndrome is a critical problem leading to an increased rate of morbidity and mortality. The present pharmacological therapies for treating anorexia-cachexia have limited effectiveness. The Japanese herbal medicine rikkunshito is often prescribed for the treatment of anorexia and upper gastrointestinal disorders. Thus, rikkunshito is expected to be beneficial for the treatment of patients with anorexia-cachexia syndrome. In this review, we summarize the effects of rikkunshito and its mechanisms of action on anorexia-cachexia. Persistent loss of appetite leads to a progressive depletion of body energy stores, which is frequently associated with cachexia. Consequently, regulating appetite and energy homeostasis is critically important for treating cachexia. Ghrelin is mainly secreted from the stomach, and it plays an important role in initiating feeding, controlling gastrointestinal motility, and regulating energy expenditure. Recent clinical and basic science studies have demonstrated that the critical mechanism of rikkunshito underlies endogenous ghrelin activity. Interestingly, several components of rikkunshito target multiple gastric and central sites, and regulate the secretion, receptor sensitization, and degradation of ghrelin. Rikkunshito is effective for the treatment of anorexia, body weight loss, muscle wasting, and anxiety-related behavior. Furthermore, treatment with rikkunshito was observed to prolong survival in an animal model of cachexia. The use of a potentiator of ghrelin signaling, such as rikkunshito, may represent a novel approach for the treatment of anorexia-cachexia syndrome.